Rechenregeln: Unterschied zwischen den Versionen
Aus RMG-Wiki
K (→Rechenregeln) |
K (→Rechenregeln) |
||
Zeile 34: | Zeile 34: | ||
a+b = b+a | a+b = b+a | ||
=2+3 = 3+2 | =2+3 = 3+2 | ||
+ | |||
a·b = b·a | a·b = b·a | ||
=2·3 = 3·2 | =2·3 = 3·2 | ||
Zeile 41: | Zeile 42: | ||
a+(b+c) = (a+b)+c | a+(b+c) = (a+b)+c | ||
=2+(3+4) = (2+3)+4 | =2+(3+4) = (2+3)+4 | ||
+ | |||
a·(b·c) = (a·b)·c | a·(b·c) = (a·b)·c | ||
=2·(3·4) = (2·3)·4 | =2·(3·4) = (2·3)·4 |
Aktuelle Version vom 22. Juni 2009, 14:48 Uhr
|